Dendritic cell actin dynamics control contact duration and priming efficiency at the immunological synapse - Leithner, Alexander (J Cell Biol, 2021)
Dendritic cells (DCs) are crucial for the priming of naive T cells and the initiation of adaptive immunity. Priming is initiated at a heterologous cell–cell contact, the immunological synapse (IS). While it is established that F-actin dynamics regulates signaling at the T cell side of the contact, little is known about the cytoskeletal contribution on the DC side. Here, we show that the DC actin cytoskeleton is decisive for the formation of a multifocal synaptic structure, which correlates with T cell priming efficiency. DC actin at the IS appears in transient foci that are dynamized by the WAVE regulatory complex (WRC). The absence of the WRC in DCs leads to stabilized contacts with T cells, caused by an increase in ICAM1-integrin–mediated cell–cell adhesion. This results in lower numbers of activated and proliferating T cells, demonstrating an important role for DC actin in the regulation of immune synapse functionality.